ANALISIS IMPLEMENTASI KEBIJAKAN PEMBERIAN DANA BANTUAN OPERASIONAL PENDIDIKAN (BOP) DALAM PENINGKATAN MUTU PENDIDIKAN SEKOLAH DASAR DI KECAMATAN BAKAU HENI KABUPATEN LAMPUNG SELATAN - MALIK Malik (Universitas Bandar Lampung (UBL), 2017)
ABSTRACTThis Research aim to picture, analysing and theoretical view of Implementation of policy of gift of fund Aid of Education Operational in make-up of quality of education of elementary school in Subdistrict Wave The Regency of Lampung Selatan, and also factors supporting and pursuing implementation of policy of gift of fund Aid of Education Operational in make-up of quality of education of elementary school in Subdistrict Wave The Regency of Lampung Selatan. This Research use the descriptive method. this Method use is to mendeskripsikan of implementation of policy of gift of relief fund of Education Operational Elementary At School Subdistrict Wave The Regency of Lampung Selatan, studying qualitative, how All data obtained is direct the than field informan by using interview and obsevasi, is and also supported by document.Result of research indicate that the Implementation of policy of gift of relief fund of Education Operational in make-up of quality of education of Elementary School in Subdistrict Wave The Regency of Lampung Selatan, have been executed and have walked, during three the last year, but its execution not yet optimal. matter Tersenut happened by because (1) Ability of executor resource not yet able to execute the program of relief fund of Education Operational better as have been determined, (2) planning which not yet good so that program the relief fund of Education Operational still is often weared for the activity of which in character insist on, like purchasing of stationery and appliance of study supporter which sometimes is not planned, inclusive of stocktaking of medium and prasarana education which not yet optimal, (3) relative the lack of pupil in one school causing the lack of operating expenses education given, because amount of Expense of Operasioan Education adapted for by a existing pupil amount in one school, and also use of medium and especial supporter education which not yet optimal. Keywords: policy implementation, aid of education operational